Respuesta :

Answer:

x = 2

Explanation:

[tex]\frac{3x-1}{5} =\frac{x+1}{3}[/tex]

First, make sure they both have common denominators ( 15 )

5 × 3 = 15 and 3 × 5 = 15

Whatever you do to the denominator you have to apply to the numerator. So, multiply the numerator and denominator of the first fraction by 3.

[tex]\frac{3*(3x-1)}{3*5}[/tex] = [tex]\frac{3(3x-1)}{15}[/tex]

Next, multiply the numerator and denominator of the second fraction by 5.

[tex]\frac{5*(x+1)}{5*3}[/tex] = [tex]\frac{5(x+1)}{15}[/tex]

Now we have: [tex]\frac{3(3x-1)}{15} =\frac{5(x+1)}{15}[/tex]

Use distributive property on the numerators of both fractions.

[tex]\frac{9x-3}{15} =\frac{5x+5}{15}[/tex]

Since the denominators are equal we can ignore them for now and find x.

9x - 3 = 5x + 5

We need to move like terms to different sides to isolate x. First, we can subtract 5x from both sides.

9x - 5x - 3 = 5x - 5x +5

4x - 3 = 5

Then, we can add 3 to both sides to cancel out the -3.

4x - 3 + 3 = 5 + 3

4x = 8

Finally, to find x we divide both sides by 4.

4x ÷ 4 = 8 ÷ 4

x = 2

ACCESS MORE